2012
DOI: 10.1136/jclinpath-2012-200854
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem analysis of bone marrow osteoclasts using tartrate-resistant acid phosphatase staining: does histochemistry work and correlate with time since death?

Abstract: This study clearly shows that BM osteoclasts stay TRAP-positive for 7 days post-mortem, although with markedly reduced TRAP-SIs compared with biopsies. Since TRAP-SIs were not correlated with the duration of PMI, TRAP staining of BM osteoclasts cannot serve as a tool to determine the time of death of a patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…The samples used to estimate the PMI came from different organs, such as brain [ 38 , 39 , 42 ], thyroid [ 35 , 36 ], pancreas [ 34 , 37 , 38 ], gingival tissue [ 14 , 27 ], skin [ 44 ], heart [ 33 , 43 ], large intestine [ 45 ], female genital system [ 46 ], bone marrow [ 40 ], skeletal muscle [ 41 ], as well as lung and liver [ 42 ]. For these tissues, the various authors used different markers, without any overlap or repetition ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples used to estimate the PMI came from different organs, such as brain [ 38 , 39 , 42 ], thyroid [ 35 , 36 ], pancreas [ 34 , 37 , 38 ], gingival tissue [ 14 , 27 ], skin [ 44 ], heart [ 33 , 43 ], large intestine [ 45 ], female genital system [ 46 ], bone marrow [ 40 ], skeletal muscle [ 41 ], as well as lung and liver [ 42 ]. For these tissues, the various authors used different markers, without any overlap or repetition ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further work on 74 subjects was conducted by Boehm et al [ 40 ], who evaluated the chronological variation of the expression of the antigenic marker Tartrate-resistant acid phosphatase (TRAP) in bone marrow. They reported that TRAP was detectable in osteoclasts with a constant intensity until the seventh day after death, after which there was a sudden and total negativity of the immunoreaction.…”
Section: Resultsmentioning
confidence: 99%
“…After µCT scanning, specimens were decalcified in an EDTA solution, dehydrated in ethanol (70%-100%), and embedded in paraffin. Sections (~5 μm) were cut transversely and stained with tartrate-resistant acid phosphatase (TRAP) stain and osteopontin (OPN) stain as established biomarkers for osteoclast and osteoblast activity, respectively (Colnot et al, 2007;Boehm et al, 2012;Bondarenko et al, 2013). Images were acquired by optical light microscopy (Carl Zeiss Micro Imaging GmbH, Göttingen, Germany).…”
Section: Paraffin Embedding and Histologymentioning
confidence: 99%
“…Recently, we have reported that tartrate-resistant acid phosphatase (TRAP) staining of autopsy samples of FFPE bone marrow (BM) was feasible in general, but TRAP staining intensities (SI) were not associated with postmortem intervals (PMI) 1. α-Naphthyl acetate esterase (ANAE) is a further enzyme of only few known to date that are detectable on FFPE BM samples.…”
Section: Introductionmentioning
confidence: 99%